A history of Christianity in Indonesia - Aritonang, Jan S.; Steenbrink, Karel A. (Studies in Christian mission, 2008)
Indonesia is the home of the largest single Muslim community of the world. This book gives the history of Christians in Indonesia during the Portuguese period (1511-1605), under Dutch colonialism (1605-1942) and more elaborate for the period of the Indonesian Republic (since 1945).